Delineating crustal domains in Peninsular India: Age and chemistry of orthopyroxene-bearing felsic gneisses in the Madurai Block - Plavsa, D; Collins, Alan; Foden, John; Kropinski, L; Santosh, M; Chetty, T.; Clark, Chris (Elsevier BV, 2012)
The Madurai Block of southern India is rich in granitic orthogneiss, much of which is orthopyroxene-bearing (charnockite). This study has identified that orthogneiss from the northwest of the Madurai Block (broadly defined as north and west of the Karur–Kambam–Painavu–Trichur lineament) has a very different origin from that in the south-eastern Madurai Block. To the north and north-west of the Madurai Block, charnockites record Neoarchaean (~2.7–2.5 Ga) crystallization ages with metamorphic overprinting at ~535 Ma. Their Archaean Nd depleted mantle model ages (2.51–3.01 Ga), high ɛNd(T) values (between −3.28 and +4.55) and low to moderate initial 87Sr/86Sr ratios (0.7017–0.7106) indicate a primarily mantle-derived origin with variable involvement of Archaean crustal material. The south-east Madurai Block samples have much younger crystallization ages of 1007 ± 23 Ma and 784 ± 18 Ma and a range of Nd depleted mantle model ages between 1.38 and 1.69 Ga, suggesting a significantly different isotopic evolution of this terrane. The isotopic signature of these charnockites (ɛNd(T) = +2.58 to −3.28, initial 87Sr/86Sr = 0.7054–0.7084) suggests the involvement of a mantle source with variable input from the contemporary crust. All samples show subsequent zircon growth, or isotopic disturbance, due to Ediacaran–Cambrian metamorphism (~535 Ma).The sharply contrasting primary igneous U–Pb ages of orthogneisses identify two distinct terranes; an Archaean basement terrane to the north and west and a Proterozoic terrane dominated by metasedimentary rocks to the south and east of the Madurai Block. The isotopic boundary between the two is here defined as a broad zone south of the Karur–Kambam–Painavu–Trichur (KKPT) lineament and appears as a southerly dipping series of seismic reflectors. A correlation is made with central Madagascar where Proterozoic metsedimentary rocks are thrust over Neoarchaean orthogneisses of the Antananarivo Block.